Analisis Manajemen Sistem Informasi Perhitungan Pasien Masuk Ruang Rawat Inap - Mulyanto, Dody; Saputro, Yanu (Journal Health Information Management Indonesian (JHIMI), 2022)
Dr. Soeradji Tirtonegoro Klaten Hospital still uses a manual system in daily services, of course this will affect health services to patients because data is not stored in electronic form. So the problem that is often encountered is the loss of data when it is needed again, in this case the data in question are daily reports, monthly reports and annual reports that are obtained from the results of daily patient calculation activities in each inpatient ward. The research method that the authors do consists of data collection methods and systems development methods. For the data collection method the author uses the method of observation, interviews, literature study, and documentation. Meanwhile, the system development method that the author uses is the waterfall method with a framework of information systems built using Laravel, the database using MySQL, and for the code editing tool using sublime text. The result of this research is a website-based information system for calculating patients into the inpatient ward of the IRJT dr.Soeradji Tirtonegoro Klaten.